Political and Legal Aspect of China-Rusia Cooperation in the Asian Super Grid - Maryam Akhmadova, Ksenia Belikova, (Opción, 2019)
The aim of the study is to investigate the political and legal aspect of China-Russia cooperation in the Asian Super Grid via comparative quantitative research methods. As a result, the key task of Russia, not only within a regional electric power cooperation project but also in the development of bilateral relations (especially with the PRC), is to provide conditions for the socio-economic development of Russian resource and transit territories. In conclusion, building up its own export potential in the electric power industry will allow Russia to strengthen its existing electric power complex in regions neighboring China.